PENGARUH MAKANAN TERHADAP SPIRITUAL DAN KESEHATAN PERSPEKTIF INTEGRASI AGAMA DAN ILMU - I Ketut Wartayasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Food that is needed by the body to affect the spiritual, of course, healthy, nutritious and perfect food so that integration and mutual influence occur between the body and the spirit from the terminology of science and religion. Just as eating food that is sattwika will behave sattwika too, in his life he has noble character. If you eat Rajasik, you will behave Rajasika and your activities are never silent, always do activities, but you don't have any responsibilities. If you only like tamasika food, you will be lazy, sluggish, careless, stupid and the like.So the influence of food on the spiritual from the point of view of science is the occurrence of the bloom of intuition, strong inner bloom, a strong soul, and the like. Likewise, the effect of food on health is that the body will become healthy and when viewed from a religious point of view the influence of food on health is influencing the behavior and spiritual character of a person in life activities is one representation of the pattern of eating and what is eaten apart from being caused by other factors. Keywords: influence of food, health, spiritual